Modeling Charitable Giving Using a Box-Cox Standard Tobit Model - Lankford, R. Hamilton; Wyckoff, James H. (The Review of Economics and Statistics, 1991)
There is a large literature investigating the determinants of charitable giving, in particular, price and income elasticities. We find that many of the most often reported results from this literature rely on a model specification that is inappropriate when applied to recent Federal Tax File data. We develop a standard Tobit model with a Box-Cox transformation parameter that nests a number of other specifications. The Box-Cox model yields estimates of price elasticities and expected charitable contributions that differ from those obtained using the typical specification. Additionally, we find that the use of sample weights provides potentially important policy insights. Copyright 1991 by MIT Press.